Tears, Fire, and Blood : The United States and the Decolonization of Africa - Meriwether, James Hunter, 1963- (Book collections on Project MUSE., 2021)
"In Tears, Fire, and Blood, James Meriwether offers a sweeping history of how the United States responded to decolonization in Africa. The new political terrain of the twentieth century drew out national and ideological dilemmas in the U.S.: democratic principles of self-determination ran up against fears of potential Communist gains, and ideals of one person/one vote crashed against doubts about weakening western alliances and anticommunist partners. A decolonizing Africa helped propel the black freedom struggle around the world, forcing the U.S. to confront the realities of civil rights abroad as it fought over how to achieve equality at home. Meriwether demonstrates that Washington veered between strengthening African nationalist movements seeking majority rule and independence and bolstering anticommunist European allies seeking to maintain white rule. Ultimately, the U.S. supported European allies and white minority rule, choosing national security interests and racial prejudices over anticolonialism"--